Association of high complement and low immunoglobulins with the clinical symptoms of patients with fibromyalgia - Satoshi Izuno; Masako Hosoi; Kozo Anno; Takahiro A. Kato; Nobuyuki Sudo; Kazufumi Yoshihara (BioPsychoSocial Medicine)
Abstract Background Fibromyalgia (FM) is a disease characterized by chronic widespread pain concomitant with various symptoms such as fatigue and anxiety. Although chronic inflammation has been implicated in the immunological abnormalities of FM, there are few human studies on complement and immunoglobulins. In this study, we investigated the immunological characteristics of FM patients and the association between their clinical symptoms and immunological indices, including complement and immunoglobulins. Methods 1) The serum 50% hemolytic complement activity (CH50), C3, C4, IgG, IgM, and hsCRP of 36 FM patients and 30 healthy sex- and age-matched controls (HC) were measured and compared. 2) Data from the Brief Pain Inventory (pain intention and pain interference subscales), the visual analog scale (VAS) (low back pain, knee pain, and fatigue), the State-Trait Anxiety Inventory and the Center for Epidemiologic Studies Depression Scale (anxiety and depression), and CH50, IgG, and hsCRP as immunological indices were acquired for 41 FM patients. Correlation analysis was done of the clinical symptom and immunological indices. Results 1) The FM group had significantly higher CH50 and lower IgG and IgM than the HC group after adjusting for body mass index (BMI). 2) Correlation analysis of immunological indices and clinical symptoms showed a positive, partial correlation between CH50 and fatigue and trait anxiety after adjusting for sex, age, and BMI. Conclusions FM patients had higher CH50 and lower immunoglobulin levels than HCs. CH50 was also associated with the fatigue and trait anxiety of FM patients. Further studies are needed to determine whether changes in these immunological indices can be used as biomarkers and/or therapeutic targets for FM.